Making Media Work: Turning to Labor Management in Communication Studies. - RODINO-COLOCINO, MICHELLE (International Journal of Communication (19328036), 2017)
This essay discusses a work in progress that explores how new media technologies promised to manage labor. From the film technologies of the early 20th century to today's smart mobile devices and algorithmic software, new media have been allied with emergent forms of labor management. Although such media, when first introduced, were clunky and unpredictable, they became key instruments in new labor management practices. Thus, this essay and the larger project it discusses contribute to the "turn to labor" in communication studies, a vibrant research area that foregrounds labor as the practice of work at both individual and social levels.